MAIN DIRECTIONS OF TRANSFORMATION OF THE SYSTEM OF PUBLIC GOVERNANCE IN THE FIELD OF HEALTHCARE IN UKRAINE IN CONDITIONS OF MARTIAL STATUS AND ARMS OF ARMED WEAPONS - Zhovnirchyk, Yaroslav; Dolot, Volodymyr; Antonov, Andrii (Public Administration and Regional Development, 2022)
The relevance of the research topic is substantiated in the article. An analysis of recent research and publications. The most acute challenges of the domestic present related to the ongoing large-scale armed aggression of the Russian Federation against Ukraine have been identified and characterized, namely: inaccessibility of medical services; deteriorating health of the population, psychological disorders. The definition and characterization of the main directions of transformation of the public health care system in Ukraine in the conditions of martial law and armed aggression of the Russian Federation against Ukraine are substantiated, namely: minimization of gender gap among health care personnel; improving the state mechanism for providing psychological assistance to the population; improving the mechanisms of interaction between public authorities in the field of health care and the volunteer movement; elaboration of a mechanism for regulating the provision of medical humanitarian aid; reorientation to the domestic manufacturer of medical products and services and medicines. The list of normative legal acts adopted by the Ministry of Health of Ukraine since the imposition of martial law in Ukraine is given as an illustration of the activity of public authorities. The expediency of the adoption of the new Law of Ukraine “On Medicinal Products” (registration № 5547 of 21.05.2021) was substantiated after the end of martial law. The list of internal and external measures to be taken by the leadership of the Ukrainian state to support the domestic economy in general and the medical sector in particular during the military invasion and martial law. It is proposed to build a military health care system in modern Ukraine. The borrowing of elements of the relevant thematic experience of such countries as Switzerland and Israel is argued. Perspective directions of further thematic theoretical and practical researches are determined. Thus, the article formulates and solves a topical scientific problem in the field of public administration, which is to substantiate the definition and characterization of the main directions of transformation of public health management in Ukraine under martial law and armed aggression of the Russian Federation against Ukraine.